2016
DOI: 10.1007/s00126-016-0672-x
|View full text |Cite
|
Sign up to set email alerts
|

The world-class Howard’s Pass SEDEX Zn-Pb district, Selwyn Basin, Yukon. Part II: the roles of thermochemical and bacterial sulfate reduction in metal fixation

Abstract: The Howard's Pass district of sedimentary exhalative (SEDEX) Zn-Pb deposits is located in Yukon Territory and comprises 14 Zn-Pb deposits that contain an estimated 400.7 Mt of sulfide mineralization grading 4.5 % Zn and 1.5 % Pb. Mineralization is hosted in carbonaceous and calcareous and, to a lesser extent, siliceous mudstones. Pyrite is a minor but ubiquitous mineral in the host rocks stratigraphically above, within, and below mineralization. Petrographic analyses reveal that pyrite has a complex and protra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 50 publications
(111 reference statements)
0
24
0
Order By: Relevance
“…TSR has also been invoked as an important process in ore deposits (Rye and Ohmoto 1974;Powell and Macqueen 1984;Ghazban et al 1990;Tompkins et al 1994;Randell and Anderson 1996;Alonso et al 1999;Cooke et al 2000;Peevler et al 2003;Kelley et al 2004aKelley et al , 2004bBasuki et al 2008;Gadd et al 2017;Sooenicka and Lüders 2018). Hydrothermal sulfate-bearing fluids that percolated through preexisting evaporites could react with organic matter and form pyrite deposits.…”
Section: Thermochemical Sulfate Reduction (Tsr)mentioning
confidence: 99%
“…TSR has also been invoked as an important process in ore deposits (Rye and Ohmoto 1974;Powell and Macqueen 1984;Ghazban et al 1990;Tompkins et al 1994;Randell and Anderson 1996;Alonso et al 1999;Cooke et al 2000;Peevler et al 2003;Kelley et al 2004aKelley et al , 2004bBasuki et al 2008;Gadd et al 2017;Sooenicka and Lüders 2018). Hydrothermal sulfate-bearing fluids that percolated through preexisting evaporites could react with organic matter and form pyrite deposits.…”
Section: Thermochemical Sulfate Reduction (Tsr)mentioning
confidence: 99%
“…Nonetheless, the processes of sulfate reduction to sulfide in different orebodies and the subsequent deposition of sulfide minerals remain controversial (Gadd et al, 2017;Magnall et al, 2016b). Thermochemical and bacterial sulfate reduction (TSR and BSR, respectively), and anaerobic oxidation of methane coupled with sulfate reduction (AOM-SR, Magnall et al, 2016b) are the most relevant processes for supplying sulfur from the seawater sulfate and deposition of sulfide minerals in SHMS deposits (e.g., Kelley et al, 2004;Shanks III, 2001, 2014Magnall et al, 2016b;Gadd et al, 2017), discussed below in stratiform and stratabound sulfide ores.…”
Section: Sources Of Sulfurmentioning
confidence: 99%
“…In particular, one of the most important reactions controlling the sulphur behavior in deep sedimentary environments is the abiogenic reduction of sulphate to sulphide (occurring at temperature above 100-140 • C) coupled with the oxidation of hydrocarbons, which is termed thermochemical sulphatet reduction (TSR) [94][95][96]. Thus, the TSR process involving hydrocarbons may contribute significantly to the genesis of both MVT and SEDEX ore deposits [97][98][99]. Moreover, it has been suggested that siliceous limestones commonly experience insignificant decarbonation/decomposition of carbonates under contact metamorphic conditions; whereas for most sedimentary rocks enriched in organic matter, CH 4 rather than CO 2 will be released [100].…”
Section: Possible Mechanisms For the Oxidation Of Hydrocarbons To Comentioning
confidence: 99%